Synergistic Effects of PdOx-CuOx Loadings on Methyl Mercaptan Sensing of Porous WO3 Microspheres Prepared by Ultrasonic Spray Pyrolysis - Nantikan Tammanoon (2020)
In this work, PdOx-CuOx co-loaded porous WO3 microspheres were synthesized with varying loading levels by ultrasonic spray pyrolysis (USP) using polymethyl methacrylate (PMMA) microspheres as a vehicle template. The as-prepared sensing materials and their fabricated sensor properties were characterized by X-ray analysis, nitrogen adsorption, and electron microscopy. The gas-sensing properties were studied toward methyl mercaptan (CH3SH), hydrogen sulfide (H2S), dimethyl sulfide (CH3SCH3), nitric oxide (NO), nitrogen dioxide (NO2), methane (CH4), ethanol (C2H5OH), and acetone (C3H6O) at 0.5 ppm under atmospheric conditions with different operating temperatures ranging from 100 to 400 °C. The results showed that the CH3SH response of USP-made WO3 microspheres was collaboratively enhanced by the creation of pores in the microsphere and co-loading of CuOx and PdOx at low operating temperatures (≤200 °C). More importantly, the CH3SH selectivity against H2S was significantly improved and high selectivity against CH3SCH3, NO, NO2, CH4, C2H5OH, and CH3COCH3 were upheld by the incorporation of PdOx to CuOx-loaded WO3 sensors. Therefore, the co-loading of PdOx-CuOx on porous WO3 structures could be promising strategies to achieve highly selective and sensitive CH3SH sensors, which would be practically useful for specific applications including biomedical and periodontal diagnoses.